HUBUNGAN KERJA ANGGOTA DEWAN PERWAKILAN DAERAH DENGAN DAERAH YANG DIWAKILI MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2019 TENTANG MAJELIS PERMUSYAWARATAN RAKYAT, DEWAN PERWAKILAN RAKYAT, DEWAN PERWAKILAN DAERAH DAN DEWAN PERWAKILAN RAKYAT DAERAH - Habby Ramadhan; Dessy Artina; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Amendments to the 1945 Constitution have resulted in several new state institutions,one of which is the Regional Representative Council (DPD). The basic idea behind theformation of the DPD is the desire to accommodate regional aspirations and at the same timegive the regions a bigger role in the process of making political decisions on matters that areprimarily directly related to the regions. With the authority possessed by the DPD manythings can be done. Now many people don't know what the DPD is, why this happenedbecause the performance of the DPD has not been optimal. Many discussions and seminarshave been held by the DPD, both with legal and political experts and with their constituentsin their respective regions, the context of these discussions always discusses the weakness ofthe authority possessed by the DPD, as if this authority is the main obstacle in carrying out itsduties and obligations. .This type of research is normative legal research. Normative legal research is legalresearch conducted by examining literature or secondary data consisting of primary legalmaterials, secondary legal materials and tertiary legal materials. Normative legal research isalso called doctrinal legal research, also referred to as library research or document study.This research examines the subject matter in accordance with the scope and identification ofproblems through a statutory approach (Statute approach). related to the legal issue understudy.The ineffectiveness of the DPD as a representative institution in carrying out its dutiesis suspected to have occurred due to several factors. First, misconceptions in applying thebicameral concept. Second, the authority of the DPD is very limited and is only related toregional matters. Third, the DPD was formed to prevent the hegemony of the executivebranch from returning, but then the balance of power did not work effectively because of thelarge amount of authority possessed by the DPR. The ideal mechanism related to theimplementation of regional community aspirations in the field of supervision carried out bythe DPD is divided into two ways in conveying aspirations, namely by formal and informalmeans. DPD members are expected by their voters to fulfill the will of the people'saspirations, provide services and provide various other forms of satisfaction even if they areonly symbolic, in carrying out their duties it is not uncommon for differences to occurbetween the representatives of the people and the people who elect them.Keywords : DPD – Authority – Settings